2022
DOI: 10.3389/fphar.2022.1009950
|View full text |Cite
|
Sign up to set email alerts
|

Risk of major adverse events associated with gabapentinoid and opioid combination therapy: A systematic review and meta-analysis

Abstract: Background: The use of opioid–gabapentinoid combinations has increased, raising several safety concerns. However, meta-analysis studies focusing on this issue are limited.Objective: To evaluate the risk of central nervous system (CNS) depression, gastrointestinal (GI) adverse events, and mortality of combination therapy compared with those of opioid therapy and to explore the differences in the results according to study design and indications.Methods: Relevant studies were selected (published before 30 Januar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 72 publications
0
10
0
Order By: Relevance
“…In 2022, Hahn et al. ( 72 ) found that opioid-gabapentin combination therapy, despite reducing gastrointestinal adverse effects, may also lead to an increased risk of central nervous system depression and death. A recent meta-analysis ( 73 ) compared the efficacy of combinations of two or more drugs with placebo or at least one monotherapy in adults with NP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2022, Hahn et al. ( 72 ) found that opioid-gabapentin combination therapy, despite reducing gastrointestinal adverse effects, may also lead to an increased risk of central nervous system depression and death. A recent meta-analysis ( 73 ) compared the efficacy of combinations of two or more drugs with placebo or at least one monotherapy in adults with NP.…”
Section: Discussionmentioning
confidence: 99%
“…Combining different medications can sometimes improve analgesia and/or tolerability (71), but the increased use of combination medications also poses some safety concerns. In 2022, Hahn et al (72) found that opioid-gabapentin TABLE 6 The common pathophysiological characteristics between neuropathic pain and Multiple sclerosis, Alzheimer's disease, Parkinson's disease and Huntington's disease.…”
Section: Treatment Of Npmentioning
confidence: 99%
“…The post-intervention SMD was calculated from the depression score after vitamin D supplementation between the intervention and placebo groups. Heterogeneity was assessed using Cochrane’s Q and I 2 statistics, with significance set at p > 0.1 and I 2 > 50% ( 33 ). A fixed-effects model was used in the absence of significant heterogeneity, and a random-effects model was used in the presence of significant heterogeneity ( 34 ).…”
Section: Methodsmentioning
confidence: 99%
“…Adverse effects of SNRIs include nausea, headache, dizziness, sweating, and arterial hypertension. Patients on gabapentinoids frequently complain of dizziness or somnolence, but both pregabalin and gabapentin are also associated with more serious adverse events, such as respiratory depression [56] and abuse [57].…”
Section: The Problem Of Neuropathic Feature In Cancer Painmentioning
confidence: 99%